Observations of hysteresis in the annual exchange circulation of a large microtidal estuary. Issue 4 (18th April 2015) - Meyers, Steven D.; Wilson, Monica; Luther, Mark. E.
Abstract A nonlinear relation between the salinity field and the subtidal exchange circulation in the Tampa Bay estuary is demonstrated using observational data from 1999 to 2011. The data are averaged to form mean monthly climatological values of total freshwater discharge ( <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjn1cq6pr" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Q</alternatives>), axial and vertical salinity gradients, and subtidal vertical shear. Well‐known steady state solutions indicate that the exchange circulation is linearly proportional to the horizontal salinity gradient, assuming a constant vertical eddy viscosity ( <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjn1cq6s9" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Aeff</alternatives>). The exchange flow is found to be multivalued with respect to the horizontal salinity gradient, forming a hysteresis loop in parameter space that passes through three dynamical regimes. Regime I is relatively dry with weak salinity gradients and exchange circulation. Regime II is the wet season (June–September) in which all quantities rapidly increase. In regime III, the exchange flow persists even though <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjn1cq6vb" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Q</alternatives> and the axial salinity gradient are again low. Gradient Richardson numbers and Simpson numbers also form a loop in parameter space with <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjn1cq6xc" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Ri</alternatives> remaining subcritical (turbulent) until the wet season when <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjn1cq6zw" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Ri</alternatives> rises above criticality (weak vertical mixing) where it remains through the end of regime III. The Simpson number is in a narrow range around 0.2, indicating that the horizontal salinity gradient is always a driver of the exchange circulation. The <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjn1cq70w" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Aeff</alternatives>, estimated from a parameterization of the Richardson number, decreases by almost an order of magnitude from regimes I to II. It remains low during III, indicating that the persistent stratification is insulating the exchange flow from destruction by tidal mixing during this time period.